Complete mitochondrial genome of green shrimp, Chlorotocus crassicornis (Crustacea: Decapoda: Pandalidae) in Korean water - GyungRyul Kim, ,- (Taylor & Francis, 2019)
he complete mitochondrial genome of green shrimp, Chlorotocus crassicornis (Costa, 1871) was generated by the combination of next-generation sequencing platform and long PCR technique. The mitochondrial genome of C. crassicornis was 16,500 bp, in which 13 protein-coding genes, two ribosomal RNAs, 22 transfer RNAs, and a putative control region was encoded. Based on the 13 protein-coding genes region, the phylogenetic tree was clearly demonstrated that C. crassicornis is closest to Pandalopsis japonica and Pandalus borealis with 77% identity. This mitogenome information will be helpful for the further studies of deep-sea fisheries resources management strategies in Korea including C. crassicornis species.